Massive Open Online Courses and Monoids - Farias, Hugo; Braga, Christiano; Menezes, Paulo B. (Formal Methods: Foundations and Applications, 2016)
Massive open online courses (MOOC) allows for distributed long-distance learning for extremely large student enrollment. Nowadays most universities throughout the world have their courses online. Web portals such as Coursera or edX join together courses from many of them. Even though there are many platforms to support the development of MOOC, such as Moodle or XBlock, it does not seem to be the case that there are many languages to help course descriptions. Moreover, we would like to allow the description of different paths to teach and learn a given subject. We propose Learn, a declarative language for course descriptions. The contribution of this paper is manyfold: (i) we exemplify Learn descriptions, (ii) formalize the meaning of Learn descriptions and teaching strategies, that allows for different teaching paths, and (iii) discuss the implementation of a toolkit to specify, analyze and generate a course in a MOOC platform from Learn descriptions.